Lenalidomide as a novel treatment for refractory acquired von Willebrand syndrome associated with monoclonal gammopathy. (27th April 2016) - Lavin, M.; Brophy, T. M.; Rawley, O.; O'Sullivan, J. M.; Hayden, P. J.; Browne, P. V.; Ryan, K.; O'Connell, N.; O'Donnell, J. S.
Abstract : Essentials Treatment options are limited for refractory bleeding in acquired von Willebrand Syndrome (AVWS). Lenalidomide therapy was studied in two patients with AVWS due to monoclonal gammopathy (MG). Lenalidomide increased von Willebrand factor (VWF), lowered VWF clearance and resolved bleeding. Lenalidomide is a potential treatment option for refractory bleeding in AVWS secondary to MG. Summary: Background: Acquired von Willebrand syndrome (AVWS) is associated with lymphoproliferative disorders, including monoclonal gammopathy (MG) of undetermined significance (MGUS) and multiple myeloma. Patients commonly present with significant bleeding complications that are difficult to manage, owing to a markedly reduced von Willebrand factor (VWF) half‐life. Objectives: To investigate the use of the immunomodulatory drug lenalidomide in two patients with severe refractory bleeding caused by AVWS associated with MGs. Results: In both patients, lenalidomide treatment resulted in significant clinical improvement, and marked increases in plasma VWF antigen (VWF:Ag) and VWF ristocetin cofactor levels. This normalization in plasma VWF levels was sustained for > 2 years in both patients. Furthermore, in one patient, plasma VWF levels remain normal for at least 14 months following discontinuation of lenalidomide treatment. To investigate the molecular mechanisms underlying these observations, VWF propeptide (VWFpp)/VWF:Ag ratios were analyzed to assess VWF clearance. At enrolment, plasma VWFpp/VWF:Ag ratios were significantly elevated in both patients. Importantly, lenalidomide treatment resulted in normalization of VWFpp/VWF:Ag ratios in both patients. These novel data suggest that lenalidomide functions to attenuate enhanced VWF clearance in AVWS. Interestingly, in a patient with MGUS, lenalidomide treatment was associated with a significant increase in plasma VWF levels, despite no major change in paraprotein level. Conclusions: Collectively, our findings suggest that lenalidomide constitutes a novel therapeutic option for the management of AVWS associated with MG. The biological mechanism(s) through which lenalidomide causes a sustained increase in plasma VWF levels in AVWS independently of paraprotein level requires further study, but is in part modulated through inhibition of enhanced VWF clearance.